Upaya Mereduksi Aksi Klitih oleh Pelajar Melalui Pelatihan Pemberdayaan Psikis dan Perilaku di Yogyakarta - Aziz Muzaki; Annurdien Rasyid; Hajidah Salsabila Allissa Fitri; Putri Milenia Gusdian; Maria Ameylia Trisna Murti; Pujianto Pujianto (Yogyakarta State University, 2022)
This community dedication aims to provide education regarding the prevention of klitih through psychological and behavioral empowerment which is implemented through the Sekolah Anti Klitih (SETITI). This activity is surely the result of collaboration with partner, in this case the partner involved is MAN 3 Sleman which is located on Jalan Magelang km. 4, Sinduadi, Mlati, Sleman, Special Region of Yogyakarta. The object determined by the partner leadership, in this case the guidance and counseling teacher of MAN 3 Sleman who is also a Scoutmaster, is the students of MAN 3 Sleman who are members of the Scouting Ambalan Council. This activity consists of training and mentoring programs. The series of activities in the training program are SETITI program socialization, focus group discussions, and soft and hard skills training. Meanwhile, the series of mentoring activities program are sharing sessions, dream posters, and SETITI festival as the culmination of the activities of this community dedication program. Increased knowledge of students related to klitih can be seen through the results of the pre-test and post-test, as well as from the behavior of students who are more disciplined after participating in a series of activities. It is hoped that the improvement shown by the target audience can be a step for the formation of klitih preventive agents.